Protection Of Children From Violence In Social Media In The New Normal Era - Aryono Aryono; Rina Arum Prastyanti (Veteran Justice Journal, 2020)
The Ministry of Women's Empowerment and Child Protection (PPPA) received thousands of reportsrelated to cases. Most of the reports submitted were about sexual violence. Deputy for Child Protection ofthe Ministry of PPPA, from the Online Information System for the Protection of Women and Children(Symfoni PPA) which was collected from January 1 to July 31, 2020. In total there were 4,116 cases. Thenumber has increased as per 18 August 2020 to 4,833 cases. Most reports were submitted from East Java,East Kalimantan, Southeast Sulawesi, and North Maluku. In detail, the 4,116 cases received by the PPASymphony consisted of 68 victims of exploitation, 73 victims of TIP, 346 victims of neglect, 979 victims ofpsychological violence, 1,111 victims of physical violence and 2,556 victims of sexual violence. This type ofresearch uses the sociolegal research method. This research requires a multidisciplinary approach toanalyze and interpret the law, the legal phenomenon, the relationship between those two and also theirrelationship with the society in its widest sense. The research approach used in this paper is the statuteapproach. The statute approach is carried out by examining all laws and regulations relating to the legalissues being addressed. The research conducted is aimed more at the approach to laws and regulationsassociated with the issue protection of children from violence in social media in the new normal era. DataAnalysis Techniques used for this study are deductive analysis methods, namely data analysis methodsstarting with general postulates and certain paradigms as a base for starting conclusions. Nationalgovernments are urged to devise and implement legislation and to harmonise laws to protect children fromall cyber crimes including online grooming, luring or stalking, exposure to illegal or inappropriatematerials and all actions related to child pornography (including creation, dissemination, accessing,downloading, possession and incitement). As such, governments are urged to classify the crime of beinginvolved (in any way) with child pornography as a crime against humanity, thereby falling under theprinciple of universal jurisdiction. Cross-border cooperation Cross-border jurisdictional issues remain abarrier for achieving comprehensive solutions.